THE INFLUENCE OF TREATMENT OF SOIL ON WATER AND PHYSICAl INDICATORS OF ITS FERTILITY AND YIELD OF EDIBLE SUBSPECIES OF CORN - Конопля, Н. И.; Маслиёв, С. В. (Scientific Progress & Innovations, 2014)
The results of long-term experiments of influence of basic treatment of soil, in particular moldboard and moldboardless plowing on 22-24 cm and shallow tillage on 10-12 cm in combination with one, two and three spring pre-sowing cultivations, on the dynamics of productive moisture reserves and water-resistant aggregates, its structure, volume weight and hardness are given. Agricultural machines for shallow tillage and moldboard and moldboardless plowing are recommended. The recommendations on mineral fertilization and terms of sowing are given. The yield of sweet corn cobs and grains of popcorn is shown. The dynamics of rejection depending on the type of tillage and its depth is analyzed.